A Smart Approach for Delivering of Risperidone using Euryale ferox Biopolymer Rate Controlling Flexi Films for Transvermillion Delivery - Bhavana Singh; N. V. S. Madhav (Technological Innovation in Pharmaceutical Research Vol. 11, 2021)
Objective: The purpose of the present study was to formulate and evaluate risperidone loaded bioflexi films for effective treatment of autism. For the preparation of bioflexi films, biopolymer was isolated from seeds of Euryale ferox (family Nymphaeaceae) by an economic method. The biopolymer recovered from the concentrate was subjected for various evaluation parameters such as infrared spectroscopy (IR), differential scanning colorimeter (DSC), scanning electron microscopy (SEM), nuclear magnetic resonance (NMR) and cell line toxicity study. Methods: The bioflexi films were prepared using this biopolymer, dextrose as flexicizer, and sween 80 as permeation enhancer in methanol and water as solvent system. Results: The formulations were characterized including uniformity of weight, drug content, folding endurance, and thickness. To study the stability of the formulations and in vitro dissolution of the experimental formulations were performed to determine the amount of risperidone present in the patches and scanning electron microscopy of the prepared bioflexi films was taken to see the drug distribution pattern. Drug-excipient interaction studies were carried out using Fourier transform infrared spectroscopic technique. In vitro dissolution studies showed that the drug distribution in the bioflexi film was homogeneous and it was found that the maximum drug release in 24 h was 99.81% with formulation EF3. In vitro skin permeation study was also conducted in a modified Franz’s diffusion cell which shows that the maximum permeation with the formulation EF3 and it was 768.50 \(μ\)g/cm2 after 24 h. Conclusion: Optimized formulations were found to be suitable for formulating in terms of physicochemical characteristics and there was no significant interaction noticed between the drug and biopolymer used.